An Analytical Study Of the Availability and Accessibility of e-Resources via Digital Library (W.r.t. Invertis University, Bareilly, Uttar Pradesh) - Mishra, Simran (Journal of Advanced Research in Library and Information Science, 2022)
This study investigates how Invertis University, Bareilly users use the library resources and services offered there. The primary goal of this study is to understand the current state of library automation in terms of digital libraries. Every aspect of education, including library and information science, has undergone a transformation because to ICT. Activities at the library include offering a variety of programmes and using a few approaches to create new services that allow users to browse, search, and access the internet. Modern technology has made it possible for libraries to operate without a staff by opening their doors to users on a free basis. Smart people, Smart Places, Smart Services, and Smart Place are the four components that make up the role of a Digital Library. For the convenience of users, the smart library features 24 hour services and auto services. providing streamlined & efficient services is a challenge for the staff and librarians. The questionnaire is the tool utilised to collect data for this study’s choice of survey research methodology. How to cite this article: Mishra M. An Analytical Study of the Availability and Accessibility of E-Resources via Digital Library (W.r.t. Invertis University, Bareilly, Uttar Pradesh). Adv Res Lib Inform Sci 2022; 9(1): 5-10.